José Luis Gómez-Martínez, Teoría del ensayo. Universidad de Salamanca, Salamanca, 1981; 165 pp. - Rafael Olea Franco (Nueva Revista de Filología Hispánica, 1984)
Se reseñó el libro: Teoría del ensayo.